(untitled) - Gardner, John W. (San Francisco, 2003)
"Liberty and duty, freedom and responsibility. That's the deal." John W. Gardner's life was dedicated to revitalizing the American Dream, a dream that must be recreated by each generation of caring citizens as they reshape it to meet the unrolling future. Now more than ever, citizens must step up and take action to create the world in which we want to live. Living, Leading, and the American Dream is an inspiration-- and a call to action. Beginning with an exploration of Gardner's life and values in his own words, this stirring and engaging collection shares Gardner's vision on personal renewal, community, leadership, and civic engagement. The essays and speeches collected in this transformational volume are founded on Gardner's belief that we as a people want freedom-- freedom at home as well as a world where freedom is possible. They are founded on his deep belief in the dignity and worth of the individual and his unshakable resolve to protect and preserve that dignity. They are founded on his belief that men and women should be empowered to achieve the best that is in them, and that we are the declared enemies of all conditions, such as disease, ignorance, or poverty, that stunt the individual and prevent such fulfillment. And they are founded on the fact that achieving these goals is difficult and requires the commitment of all citizens. The essays in Living, Leading, and the American Dream move from individual to community to society, offering Gardner's vision on the role of the individual in attaining the greater good. Leaders of innovative organizations, civic leaders, and concerned citizens will find guidance and inspiration in Gardner's unique vision of every citizen's responsibility and capacity to make a difference.
Keywords: Political participation,Civil society,Social values; United States,United States,United States